2019
DOI: 10.1016/j.dib.2019.104582
|View full text |Cite
|
Sign up to set email alerts
|

Data on soil properties and halophilic bacterial densities in the Na Si Nuan Secondary Forest at Kantharawichai District, Maha Sarakham, Thailand

Abstract: Saline soil is one of the most crucial problems of arid and semiarid regions because it reduces growth of plant and microorganisms. In Thailand, the inland saline soils are found mostly in the northeastern part especially in Maha Sarakham Province where 85% of the province has geological characteristics as rock salt beds. Saline soil often experiences low soil fertility problems which multiply the adverse effects on plant growth. Interestingly, the Na Si Nuan Secondary Forest, Kantharawichai District, Maha Sar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Observations also showed that the N concentration of rice plants decreased with increasing salinity in all treatments. Chookietwattana [21] reported that high soil salinity can increase osmotic stress for plants so that plants are not able to absorb nitrogen optimally. On the other hand, the nitrogenase enzyme produced by bacteria is thought to be inactive under certain saline conditions.…”
Section: Table 2 Effect Of Endophytic Bacterial Biofertilizer and Soi...mentioning
confidence: 99%
“…Observations also showed that the N concentration of rice plants decreased with increasing salinity in all treatments. Chookietwattana [21] reported that high soil salinity can increase osmotic stress for plants so that plants are not able to absorb nitrogen optimally. On the other hand, the nitrogenase enzyme produced by bacteria is thought to be inactive under certain saline conditions.…”
Section: Table 2 Effect Of Endophytic Bacterial Biofertilizer and Soi...mentioning
confidence: 99%
“…The teichoic acids found in the cell walls of Gram-positive bacteria provide the negative charges of the cell surface as a whole, thus increasing the mobility and transport of these bacteria in the environment. These findings may also be due to an extremely low amount of soil organic matter and total nitrogen in the soil samples (Chookietwattana & Yuwa-amornpitak, 2019) since Gram-positive bacteria are more prevalent in soil of low quality, while Gramnegative bacteria dominates in soils of higher quality (Zhou et al, 2017). A total of 50 out of the 55 isolates were Gram-positive rods and endospore-forming.…”
Section: Isolation Of Bacteria From Soil Samples and Phenotypic Charamentioning
confidence: 99%